SALINITY INDUCED CHANGES IN THE LEAF ANATOMY OF THE MANGROVE Avicennia marina ALONG THE ANTHROPOGENICALLY STRESSED TROPICAL CREEK - M.U. Borkar; Athalye R.P.; Quadros Goldin (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The mangrove Avicennia marina is a dominant mangrove along the anthropogenically stressed tropical Thane creek, west coast of India. Leaf anatomy of the mangrove along the Thane creek, was assessed in relation to stationwise and seasonwise variations in salinity. It was noticed that under the conditions of higher salinity, Avicennia marina showed increased thickness of hypodermal water storage tissue in the leaf (for conservation of water) and produced taller salt extruding glands at the lower epidermis to eliminate more salt; whereas, the thickness of the photosynthetic mesophyllic tissue significantly reduced. At lower salinity or with reduction in salinity in monsoon, contrary to above occurred. These changes probably explain the stunted growth of Avicennia marina in high salinity environment and its vigorous growth at lower salinity.